DEVELOPMENT OF A LITHIUM-ION BATTERY CHARGING SYSTEM UNDER CONSTANT CURRENT AND VOLTAGE CONDITIONS USING STM-32 BASED ON FUZZY LOGIC CONTROL - Asy'ari, Muhammad Khamim; Panggabean, David Keyvin Sabam Halomoan; Musyafa, Ali; Ginting, Kevin Bestian (Indonesian Physical Review, 2025)
Lithium-ion batteries are electrical energy storage devices often found in portable electronic equipment. Overcharging and discharging the battery will reduce its life and cause severe damage. Constant current and voltage control methods and control algorithms, such as fuzzy logic control, need to be added to avoid this. This research aims to develop a lithium-ion battery charging system using a constant current and voltage method based on fuzzy logic control. A constant current-constant voltage (cc-cv) charging system helps control the charging voltage and current by conditioning the initial charging to use a constant current so as not to overcharge. Constant current uses a buck converter circuit, while constant voltage uses a voltage regulator circuit. The charging system is equipped with a voltage sensor and a current sensor. System control uses fuzzy logic control methods with input variables as errors and delta errors while the output is a duty cycle. The overall system design was carried out at the Measurement, Reliability, Risk, and Safety Laboratory, ITS for 4 months. The test results show that charging the battery produces a voltage of 12.6 Volts and a current of 2.5 Amperes. The battery will be fully charged, and the charging system will stop when the flowing current decreases and the current is cut off at 100 mA.